Valerijus Čekmonas: kalbų kontaktai ir sociolingvistika. Sudarė Laima Kalėdienė. Vilnius: Lietuvių kalbos institutas, 2017. 1110 p. ISBN 978-609-411-201-0. - Ušinskienė, Viktorija (Slavistica Vilnensis, 2020)
The book under review is dedicated to the work of an outstanding linguist Prof. Valerijus Čekmonas (1937–2004). The purpose of compiling this publication was to reveal an original methodology for studying the interaction of the Baltic and Slavic languages developed by Čekmonas, who was the first in the history of linguistics to consistently substantiate explanations of concrete linguistic phenomena not only using diachronic, but also synchronic data by applying a diachronic research programme he developed. Alongside the methodology for interpreting diachronic facts, Čekmonas created a methodology for selection, grouping and storage of synchronic facts – to be called a socio-linguistic methodology – which doubled his scientific merits. The first part of the book includes twenty five the most significant articles of V. Čekmonas on the interaction of the Lithuanian, Belarusian and Polish languages. Some articles were drawn up together with co-authors, this perfectly reflects Čekmonas’ ambition to focus on solving the problem in the joint work of co-workers and to force them to take responsibility for the continuation of the work. In the second part of the book V. Čekmonas’ School is presented, there are twelve articles prepared of his followers and colleagues.